(untitled) (Research, Society and Development, 2025)
Autism spectrum disorder (ASD) is part of the Global Developmental Disorders (GDD) group, which includes other neurodevelopmental disorders in addition to ASD. According to the Centers for Disease Control and Prevention (CDC), in recent years there has been an increase in the prevalence of ASD, with a probable growth in the identification of genes associated with the syndrome. This review aims to update information from gene association studies and verify the association with ASD and its prevalence, conducted following the rigor and recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) tool. Five databases were used, obtaining a survey of 4,404 articles, and 14 studies were selected which also highlighted the influence of 56 possible candidate genes associated with the prevalence of ASD. The SHANK3 gene was found to be the most associated with the increased prevalence of ASD, followed by the SCN2A and PARD3 genes. In conclusion, the candidate genes analyzed are associated with characteristics of the syndrome, with the SHANK3 gene being the most responsible for the increased prevalence in gene association studies. However, in-depth studies need to be conducted in order to bring robustness to this field of research.